Value of PCR for Detection of Toxoplasma gondii in Aqueous Humor and Blood Samples from Immunocompetent Patients with Ocular Toxoplasmosis - Bou, Germán (American Society for Microbiology, 1999)
Toxoplasma gondii infection is an important cause of chorioretinitis in the United States and Europe. Most cases of Toxoplasma chorioretinitis result from congenital infection. Patients are often asymptomatic during life, with a peak incidence of symptomatic illness in the second and third decades of life. Diagnosis is mainly supported by ophthalmological examination and a good response to installed therapy. However, establishment of a diagnosis by ophthalmological examination alone can be difficult in some cases. To determine the diagnostic value of PCR for the detection of T. gondii, 56 blood and 56 aqueous humor samples from 56 immunocompetent patients were examined. Fifteen patients with a diagnosis of ocular toxoplasmosis had increased serum anti-T. gondii immunoglobulin G levels but were negative for anti-T. gondii immunoglobulin M (group 1), and 41 patients were used as controls (group 2). Samples were taken before antiparasitic therapy was initiated, and only one blood sample and one aqueous humor sample were obtained for each patient. Single nested PCRs and Southern blot hybridization were performed with DNA extracted from these samples. The results obtained showed sensitivity and specificity values of 53.3 and 83%, respectively. Interestingly, among all patients with ocular toxoplasmosis, a positive PCR result with the aqueous humor sample was accompanied by a positive PCR result with the blood sample. This result suggests that ocular toxoplasmosis should not be considered a local event, as PCR testing of blood samples from patients with ocular toxoplasmosis yielded the same result as PCR testing of aqueous humor samples. PCR testing may be useful for discriminating between ocular toxoplasmosis and other ocular diseases, and also can avoid the problems associated with ocular puncture.